Design of a solution technique based on an integral approach for the Flexible Open-Flow Shop scheduling problem (2018)
In manufacturing industries, scheduling is a form of decision-making that plays a crucial role. The determination of the methods by which a set of jobs must be manufactured in order to seek specific goals leads to the development of different schedule techniques. However, scheduling depends on the type of workshop or manufacturing environment such as open shop, job shop and flow shop. There are cases that more than one environment for the same manufacturing process could coexist. This project deals with a specific scheduling problem in which each job is processed under the combination of two shop environments; the first one is related to an open shop while the second one corresponds to a flow shop; this problem is called the Flexible open-flow shop (FOFS). These types of scheduling problems present NP-hardness, meaning the neediness of sophisticated algorithms to find solutions in reasonable computational times. Additionally, are commonly solved separately or by approximating into another workshop, leaving the interaction of both environments irrelevant. Thus, the main objective of this project is to design solution techniques based on an integral approach to minimize the maximum completion time also known as makespan.